Prevalence and Risk Factors for Intraoperative Hypotension during Craniotomy for Traumatic Brain Injury - Sharma, Deepak (2012)
BACKGROUND: Hypotension after traumatic brain injury (TBI) is associated with poor outcomes. However, data on intraoperative hypotension (IH) are scarce and the effect of anesthetic agents on IH is unknown. We examined the prevalence and risk factors for IH, including the effect of anesthetic agents during emergent craniotomy for isolated TBI. METHODS: A retrospective cohort study of patients ≥ 18 years who underwent emergent craniotomy for TBI at Harborview Medical Center (level-1 trauma center) between October 2007 and January 2010. Demographic, clinical and radiographic characteristics, hemodynamic and anesthetic data were abstracted from medical and electronic anesthesia records. Hypotension was defined as systolic blood pressure (SBP) < 90 mmHg. Univariate analyses were performed to compare the clinical characteristics of patients with and without IH and multiple logistic regression analysis was used to determine independent risk factors for IH. RESULTS: Data abstracted from 113 eligible patients aged 48±19 years was analyzed. Intraoperative hypotension was common (n=73, 65%) but not affected by the choice of anesthetic agent. Independent risk factors for IH were multiple Computed Tomographic (CT) lesions (AOR 19.1 [95% CI: 2.08–175.99]; p=0.009), SDH (AOR 17.9 [95% CI: 2.97–108.10]; p=0.002), maximum CT lesion thickness (AOR 1.1 [95% CI: 1.01–1.13]; p=0.016), and anesthesia duration (AOR 1.1 [95% CI: 1.01–1.30]; p=0.009). CONCLUSION: Intraoperative hypotension was common in adult patients with isolated TBI undergoing emergent craniotomy. The presence of multiple CT lesions, subdural hematoma, maximum thickness of CT lesion and longer duration of anesthesia increase the risk for IH.